Hydroxyurea blunts mitochondrial energy metabolism and osteoblast and osteoclast differentiation exacerbating trabecular bone loss in sickle cell mice - Ashish Kumar Tripathi; Sadaf Dabeer; Jun Song; Tatyana Vikulina; Susanne Roser-Page; Jessica A. Alvarez; David. R. Archer; M. Neale Weitzmann (Cell Death and Disease)
Abstract Sickle cell disease (SCD) is a severe hematological disorder characterized by erythrocyte sickling that causes significant morbidity and mortality. Skeletal complications of SCD include a high incidence of bone loss, especially in vertebrae, leading to fragility fractures that contribute to disease burden. Whether hydroxyurea (HU), a front-line therapy for SCD ameliorates bone disease has not been established. To investigate HU action on SCD-related vertebral defects, we used HU-treated “Townes” mice, an SCD animal model and performed high-resolution micro-computed tomography (µCT) imaging to resolve bone volume and micro-architectural structure of cortical and trabecular bone, the two major compartments contributing to bone mass and strength. Our data revealed that cortical bone was significantly diminished in the vertebrae of skeletally mature (representing adults) and immature (representing children) SCD mice, while only mature mice lost trabecular bone mass. Administration of HU ameliorated cortical bone loss in mature SCD mice, but paradoxically promoted trabecular bone decline in both groups. We further investigated the mechanisms of HU action in wild-type C57BL6/J mice. HU caused dose-dependent trabecular bone loss due to diminished osteoclast and osteoblast function, indicative of a low bone turnover state. Mechanistic investigations in vitro revealed that HU impeded osteoblast-progenitor proliferation and early differentiation, and diminished osteoclastogenic cytokine production, blunting osteoclast formation as well as the activity of mature osteoclasts. HU further, suppressed mitochondrial, but not glycolytic energy metabolism in both differentiating osteoblasts and differentiated osteoclasts. Collectively, these findings reveal that despite ameliorating cortical bone loss, HU inhibits trabecular bone formation and resorption, by suppressing mitochondrial energy metabolism and blunting the differentiation and/or activity of osteoblasts and osteoclasts. Together HU drives a low bone turnover state culminating in trabecular bone loss. Further investigation into HU’s impact on bone in SCD patients is warranted for understanding and managing skeletal complications in this population.